Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Pada PT. Sunlife Financial Cabang Kota Medan - Nasution, Alya Mahpuja; Bi Rahmani, Nur Ahmadi; Armayani Hasibuan, Reni Ria (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study aims to find out and analyze how and how much influence Sales Effect Work Motivation and Environment Work on Employee Job Satisfaction at PT. SUNLIFE Financial Branch Medan city. The research method used in this research is quantitative method descriptive approach. The type of data used is data Primary obtained by distributing questionnaires to employees at PT. Sunlife Medan Branch. The subject in this research is PT. Sunlife Branch Medan and the object of this research is Employee Job Satisfaction, Work Motivation and Employee Work Environment. The test equipment used in this study is Spss20 to test the classical assumptions, multiple regression analysis, and test hypothesis. Based on the results of hypothesis testing, namely the t test shows that motivation Work has a positive and significant effect on Employee Job Satisfaction with a t-count value of 3.9777 and a prob of 0.0000 <0.05. As well as Work Environment with test results that the Work Environment has a positive effect and significant to Employee Job Satisfaction with a t value of 5,972 and prob value 0.0000<0.05. And the results of the F test show that the variable Work Motivation and Work Environment simultaneously have a significant effect on Employee Job Satisfaction at PT. SUNLIFE Financial City Branch Medan with a value of F Prob 0.0000. The results of this test indicate that the variable Work Motivation and Work Environment contribute 76.9% on the variable Employee Job Satisfaction at PT. SUNLIFE Financial Branch Medan city.